การศึกษาการปนเปื้อนของฝุ่นละอองรวมภายในและภายนอกอาคาร (A STUDY ON CONTAMINATION OF TOTAL SUSPENDED PARTICULATE IN AND OUT OF BUILDING) - ปัญญาปิง, กลิ่นประทุม; วิจิตรพงษา, ปิยรัตน์; มีเพชร, วัลลี; เตจารังสี, สุพัตรา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2014)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการปนเปื้อนของฝุ่นละอองรวม (Total Suspended Particulate, TSP) ในบรรยากาศที่อยู่ภายในและภายนอกอาคารเรียน คณะวิศวกรรมศาสตร์ (ยธ.4) มทร.ล้านนา เชียงใหม่ และสิ่งปนเปื้อนในฝุ่นละอองรวม รวมทั้งความเข้มข้นเฉลี่ยของการรับสัมผัสโดยทำการเก็บตัวอย่างรวม 3 จุด จำนวนจุดละ 30 ตัวอย่าง ด้วยเครื่องเก็บตัวอย่างอากาศเฉพาะบุคคล และอีก 1 จุด ด้วยเครื่องเก็บตัวอย่างอากาศปริมาตรสูง จำนวน 40 ตัวอย่าง และทำการวิเคราะห์แบบชั่งน้ำหนัก (Gravimetric) ส่วนสิ่งปนเปื้อนในฝุ่นละอองรวม ถูกตรวจหาด้วยกล้องจุลทรรศน์แบบใช้แสงในระหว่างเดือนมีนาคม-ธันวาคม พ.ศ. 2554 ผลการศึกษาพบว่า ความเข้มข้นของ TSP ภายในอาคาร ได้แก่ ห้องเรียนยธ.4-302 มีค่า 123.8188 µg/m3 และห้องเรียนยธ.4-304 มีค่า 127.7387 µg/m3 ความเข้มข้นของ TSP ภายนอกอาคารบริเวณชั้น 2 ด้านข้างห้องปฏิบัติการทางชีววิทยา สาขาวิชาวิศวกรรมสิ่งแวดล้อม มีค่า 254.2876 µg/m3 และบริเวณชั้น 1 ด้านหลังห้องปฏิบัติการทางเคมีของสาขาวิชาเดียวกัน มีค่า 131.0608 µg/m3 สิ่งปนเปื้อนที่พบใน TSP ภายในอาคารจากทั้งสองห้องเรียน ได้แก่ อนุภาคฝุ่นละออง (100%) เศษไม้ (57, 63%) ใยหิน (Asbestos) (33, 43%) และเถ้าลอย (fly ash) (27, 37%) ส่วนสิ่งปนเปื้อนที่พบใน TSP บริเวณภายนอกอาคารทั้งสองแห่ง ได้แก่ อนุภาคฝุ่นละออง (100%) เถ้าลอย (43, 60%) ใยหิน (Asbestos) (37, 55%) เศษเหล็ก (48%) เส้นใยสังเคราะห์ (38%) เศษไม้ (30%) และอื่นๆ (<20%) และยังพบว่าค่าความเข้มข้นเฉลี่ยของ TSP ที่รับสัมผัสได้ภายในห้องเรียนของอาคารยธ.4 ในระยะเวลา 2 ชั่วโมง (30.9547, 31.9347 µg/m3) มีค่ามากกว่าในระยะเวลา 4 ชั่วโมง (61.9094, 63.8694 µg/m3) ประมาณ 2 เท่า คำสำคัญ: ฝุ่นละอองรวม สิ่งปนเปื้อน อาคาร ความเข้มข้นเฉลี่ยที่รับสัมผัส The purpose of the this study was to determine the quantity of total suspended particulate, TSP in ambient air both in and out of Faculty of Engineering Building (C-4) in Rajamangala University of Technology Lanna, Chiang Mai. The physical characteristic of contaminant and concentration exposure of TSP were also determined. It was performed by using personal air sampler for 3 sampling points, and high volume air sampler for 1 sampling point. The total number of air sample from personal air sampler was 30 samples for each sampling point, and the total number of air sample from high volume air sampler was 40 samples. All samples were analyzed by gravimetric method, and contaminants in TSP were determined by light microscope during March-December 2011. It was found that concentrations of TSP in building C-4; R4-302 and R4-304 were 123.8188 mg/m3, and 127.7387 mg/m3, respectively. The concentrations of TSP outside building C-4 in the 2nd floor where was near the Biological Laboratory (Bio. Lab.) of Environmental Engineering Dept., and in the 1st floor where was near the Chemical Laboratory (Chem. Lab.) of the same Dept. were 254.2876 mg/m3, and 131.0608 mg/m3, respectively. The physical characteristics of contaminants in TSP in the building C-4 from 2 classrooms were found to be TSP (100%), wood scrap (57, 63%), asbestos (33, 43%), and fly ash (27, 37%). The contaminants in TSP outside that building from near Bio. and Chem. Lab. were found to be TSP (100%), fly ash (43, 60%), asbestos (37, 55%), iron scrap (48%), fiber (38%), wood scrap (30%), and others (<20%). Moreover, the average concentrations of TSP exposure in the building C-4 from two classrooms in 2 hours (30.9547, 31.9347 mg/m3) were higher than those in 4 hours (61.9094, 63.8694 mg/m3) about 2 times. Keywords: Total Suspended Particulate, Contamination, Building, Time Weighted Average Exposure